Organic Three-Component Single Crystals with Pseudo-Isomorphic Cocrystallization for Nonlinear Optics and THz Photonics - Shin, Myeong Hoon; Lee, Seung Heon; Kang, Bong Joo; Jazbinšek, Mojca; Yoon, Woojin; Yun, Hoseop; Rotermund, Fabian; Kwon, O. Pil (Advanced Functional Materials, 2018)
A new organic three-component single crystals are developed using the so-called “pseudo-isomorphic cocrystallization” for nonlinear optical and terahertz (THz) photonic applications. The pseudo-isomorphic cocrystallization is based on two homocrystals exhibiting similar molecular ordering feature in the crystalline state, but different crystallographic space groups. Such new organic cocrystals consist of three components, highly nonlinear optical 2-(4-hydroxystyryl)-1-methylquinolinium (OHQ) cation, and two different counter anions. Compared to homocrystals having two components (OHQ cation and a single anion type), OHQ-based cocrystals by isomorphic cocrystallization from isomorphic homocrystals exhibit an isomorphic crystal structure with very similar physical properties. In contrast, OHQ-based cocrystals by pseudo-isomorphic cocrystallization provide a different molecular ordering with a different crystallographic space group, resulting in remarkably distinguishable crystal characteristics and physical properties, while maintaining large macroscopic optical nonlinearity with excellent optical quality and morphology suitable for diverse optical experiments. To show a potential for nonlinear optical applications, THz wave generation is demonstrated by optical rectification pumped at fundamental wavelength of 1300 nm. A 0.92 mm thick OHQ-based cocrystal by pseudo-isomorphic cocrystallization delivers efficient optical-to-THz conversion with one order of magnitude higher peak-to-peak THz electric field than the 1.0 mm thick inorganic standard ZnTe crystal and presents a broad spectral bandwidth of up to 8 THz.
Keywords: Cocrystallization; Crystal characteristics; Fundamental wavelength; Nonlinear optical applications; Optical experiments; Optical nonlinearity; Optical rectifications; Organic crystal; cocrystallization; nonlinear optics; organic crystals; terahertz waves